Fracture behavior of metallic sodium and implications for battery applications. Issue 12 (26th October 2022) - Shin, Jungho; Pharr, Matt
Abstract : We report fracture behavior of sodium metal and discover that Na is nearly insensitive to the presence of flaws. We also identify microstructural features of the fracture process and discuss the corresponding implications for battery applications. Abstract : Sodium metal has emerged as a candidate anode material in rechargeable batteries owing to its high theoretical capacity, low standard reduction potential, and abundance in the earth's crust. Prior to practical deployment, it is critical to thoroughly assess sodium's mechanical properties, as to fully understand and thus help mitigate potential failure mechanisms. Herein, we examine the fracture behavior of sodium metal through tensile tests in an inert environment. We find that sodium is nearly insensitive to flaws (crack-like features), i.e., its effective strength is virtually unaffected by the presence of flaws. Instead, under tension, sodium exhibits extreme necking that leads to eventual failure. We also characterize the microstructural features associated with fracture of sodium through scanning electron microscopy studies, which demonstrate several features indicative of highly ductile fracture, including wavy slip and microvoid formation. Finally, we discuss the implications of these experimental observations in the context of battery applications.